The Development of Collective Bargaining in the Toronto Printing Industry in the Nineteenth Century - Zerker, Sally (Relations industrielles / Industrial Relations, 1975)
Analysts of collective bargaining have tended to stress predominant functional characteristics, in general classed as marketing, governmental, and managerial theories. Less emphasis has been placed on the importance of power relation-ships between organizations. A careful review of the development of collective bargaining in the Toronto printing industry in the nineteenth century suggests that the latter is the most significant factor in the historical process.